How the New Technologies Shapes the Understanding of the Political Act: the case of Digital Vigilantism - Dementavičienė, Augustė (Politologija, 2019)
This paper is part of a bigger project where I try to evaluate and merge different philosophical and sociological approaches in order to understand and show how new technologies could change political life. This article aims to propose conceptual instruments suitable for that endeavor through the analysis of a small example of postmodern life – Digital Vigilantism – and based on ideas of Daniel Trottier, Zygmunt Bauman, and Michel Foucault. The swarm is a metaphor used by Zygmunt Bauman to show how the understanding of communities is changed in liquid modernity. Swarms are based on untied, uncontrolled, short-term relationships between consumers/users that are formed with the express purpose of achieving some goals. Swarms could be massive in numbers and have a lot of power for a quite short period. One such example could be Digital Vigilantism, which is an act of punishing certain citizens – those believed to be deserving of punishment by Internet users. One particular form of digital vigilantism is disclosing someone’s personal information (addresses, phone numbers, emails, Facebook accounts, etc.) for everybody to see in order to spread shaming acts. The acts of DV sometimes gain enough power to change the political agenda. The problem is that the interest of people to solve certain issues is often extremely short; meanwhile, a sustainable political act/change requires an active and stable effort for a much longer period. The main intrigue lies in whether the political act itself can change from being influenced by the swarm effect.